Upaya Masyarakat dalam Penanggulangan Polusi Udara Akibat Asap Pabrik Geo Dipa Dieng Banjarnegara - Ma’rifah, Nur Sofia (Al-DYAS, 2023)
Air pollution caused by factory smoke is a serious environmental issue in many regions. Dieng, Banjarnegara, is one of the areas affected by air pollution from Geo Dipa factory smoke. Air pollution can have negative impacts on human health and the surrounding environment. Therefore, efforts to mitigate air pollution are crucial. This abstract discusses the community efforts in combating air pollution from Geo Dipa factory smoke in Dieng, Banjarnegara. The research method used is a descriptive approach by collecting data through a literature review and interviews with local communities. The research findings indicate that the Dieng community in Banjarnegara has made several efforts in tackling air pollution from Geo Dipa factory smoke. Firstly, they have formed community groups that care about the environment and actively monitor the factory's activities and air quality around the facility. These groups also hold regular meetings to discuss air pollution mitigation strategies. Additionally, the community conducts environmental awareness campaigns to the surrounding community to reduce air pollution in their environment. They educate the public about the importance of maintaining environmental cleanliness and reducing the use of hazardous substances that can contribute to air pollution. Moreover, the community advocates to the local government for stricter monitoring of Geo Dipa factory activities. They submit petitions and participate in public meetings to fight for their rights to clean air and a healthy environment. In their efforts to combat air pollution, the community also supports the development of environmentally friendly alternative energy sources. They promote the use of renewable energy, such as solar and wind energy, as cleaner and more sustainable alternatives. Overall, the Dieng community in Banjarnegara has shown a strong commitment to addressing air pollution caused by Geo Dipa factory smoke. Through community environmental groups, awareness campaigns, government advocacy, and support for alternative energy development, they strive to create a cleaner and healthier environment for the common good. These efforts are crucial as an initial step in improving air quality in Dieng, Banjarnegara, and can serve as an example for other regions facing similar issues.